PGA Estimates for Vertical Ground Motion and Varying Deep Geology Site Surroundings—A Case Study of Banja Luka - Borko Bulajić; Silva Lozančić; Senka Bajić; Anka Starčev-Ćurčin; Miloš Šešlija; Miljan Kovačević; Marijana Hadzima-Nyarko (Applied Sciences, 2025)
Vertical PGA is frequently included in civil engineering regulations simply by multiplying the horizontal PGA by a constant. Moreover, most design codes, including Eurocode 8, do not consider the impact of the local soil on vertical ground motion at all. In this study, we demonstrate that such practices increase earthquake risks. The article examines vertical PGA strong-motion estimations for the city of Banja Luka. Banja Luka serves as a case study for areas with records of moderate to strong earthquakes and diverse deep geological conditions. Regional equations for scaling vertical PGA are presented. The vertical PGA values and vertical to horizontal PGA ratios are calculated and analyzed. The findings indicate that the vertical to horizontal PGA ratios for the rock sites depend on the source-to-site distance and deep geology and fall between 0.30 and 0.66. Hence, these ratios cannot be approximated by a single value of 0.90 and 0.45, as specified by Eurocode 8 for Type 1 and Type 2 spectra, respectively. Moreover, the results show that the deep geology effects on vertical ground motion can exceed the local soil effects. When the amount of recorded data from comparable areas increases, we will be able to properly calibrate the existing scaling equations and obtain more reliable estimates of vertical PGA.